Focal Adhesion Kinase Promotes Hepatic Stellate Cell Activation by Regulating Plasma Membrane Localization of TGFβ Receptor 2. Issue 2 (20th December 2019) - Chen, Yunru; Li, Qing; Tu, Kangsheng; Wang, Yuanguo; Wang, Xianghu; Liu, Dandan; Chen, Chen; Liu, Donglian; Yang, Rendong; Qiu, Wei; Kang, Ningling
Abstract : Transforming growth factor β (TGFβ) induces hepatic stellate cell (HSC) differentiation into tumor‐promoting myofibroblast, although underlying mechanism remains incompletely understood. Focal adhesion kinase (FAK) is activated in response to TGFβ stimulation, so it transmits TGFβ stimulus to extracellular signal‐regulated kinase and P38 mitogen‐activated protein kinase signaling. However, it is unknown whether FAK can, in return, modulate TGFβ receptors. In this study, we tested whether FAK phosphorylated TGFβ receptor 2 (TGFβR2) and regulated TGFβR2 intracellular trafficking in HSCs. The FAKY397F mutant and PF‐573, 228 were used to inhibit the kinase activity of FAK, the TGFβR2 protein level was quantitated by immunoblotting, and HSC differentiation into myofibroblast was assessed by expression of HSC activation markers, alpha‐smooth muscle actin, fibronectin, or connective tissue growth factor. We found that targeting FAK kinase activity suppressed the TGFβR2 protein level, TGFβ1‐induced mothers against decapentaplegic homolog phosphorylation, and myofibroblastic activation of HSCs. At the molecular and cellular level, active FAK (phosphorylated FAK at tyrosine 397) bound to TGFβR2 and kept TGFβR2 at the peripheral plasma membrane of HSCs, and it induced TGFβR2 phosphorylation at tyrosine 336. In contrast, targeting FAK or mutating Y336 to F on TGFβR2 led to lysosomal sorting and degradation of TGFβR2. Using RNA sequencing, we identified that the transcripts of 764 TGFβ target genes were influenced by FAK inhibition, and that through FAK, TGFβ1 stimulated HSCs to produce a panel of tumor‐promoting factors, including extracellular matrix remodeling proteins, growth factors and cytokines, and immune checkpoint molecule PD‐L1. Functionally, targeting FAK inhibited tumor‐promoting effects of HSCs in vitro and in a tumor implantation mouse model. Conclusion: FAK targets TGFβR2 to the plasma membrane and protects TGFβR2 from lysosome‐mediated degradation, thereby promoting TGFβ‐mediated HSC activation. FAK is a target for suppressing HSC activation and the hepatic tumor microenvironment. Abstract :